2017
DOI: 10.4314/njtd.v13i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extraction process parameters on the quality characteristics of <i>Parinari polyandra B</i>. seed oil

Abstract: Extraction process parameters can influence the quality of oil obtained from seeds during extraction process. The effect of extraction process parameters on the quality of parinari seed oil, a potential renewable industrial raw material, is yet to be reported. This research was aimed at investigating the effects of some extraction process parameters on some quality characteristics of parinari oil (acid, iodine and saponification values). This work reports for the first time the effects of extraction process pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Higher saponification values are indicative of the presence of lower molecular weight compounds/short chain fatty acids in the oil. Higher saponification value is more desirable when considering oil for soap industry and undesirable for production of biodiesel [13]. This finding is in agreement with those reported by [15,13,7].…”
Section: Extraction Proceduressupporting
confidence: 90%
See 1 more Smart Citation
“…Higher saponification values are indicative of the presence of lower molecular weight compounds/short chain fatty acids in the oil. Higher saponification value is more desirable when considering oil for soap industry and undesirable for production of biodiesel [13]. This finding is in agreement with those reported by [15,13,7].…”
Section: Extraction Proceduressupporting
confidence: 90%
“…The double bond in the oil provide the active site and once the double bond is converted to single bond the oil becomes less or nonreactive. Neem oil with lower iodine value is good for long term storage before usage due to its saturated condition [13]. Authors such as [20,7] investigated and showed the decrease of iodine value of neem seed oil as temperature increases.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Hence, the selection of appropriate types of solvent is the key factor that determines oil yield. Satriana et al 140 indicated that the quantity and quality of the oil extracted using the solvent extraction method are influenced by the types and concentrations of solvent, the types of extraction techniques employed, the temperature, and the particle size of the feedstocks, as also mentioned by Odetoye et al 141 Pereira et al 142 investigated the effect of using different solvent types (compressed propane at 30-60 °C and pressures of 2-8 MPa, n-hexane, and ethanol) and extraction methods (subcritical fluid extraction, Soxhlet, and ultrasound-assisted extraction) on oil yield from yellow passion fruit seeds, and the results revealed that Soxhlet extraction using n-hexane followed by compressed propane at 30 °C and 8 MPa provided a higher oil yield of 26.12% and 24.68%, respectively. Keneni et al 143 studied the effect of different extraction solvents on jatropha seed, indicating that solvents have different extraction capacities and efficiencies, which in turn influence the oil's quantity and quality.…”
Section: Chemical Extraction Methodsmentioning
confidence: 92%
“…Satriana et al 140 . indicated that the quantity and quality of the oil extracted using the solvent extraction method are influenced by the types and concentrations of solvent, the types of extraction techniques employed, the temperature, and the particle size of the feedstocks, as also mentioned by Odetoye et al 141 . Pereira et al 142 .…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 94%
“…Oil production could be of interest in places with dense tree populations, but in most cases domestication would be needed to ensure supplies. Based on high oil content (56%) and the high content of α-eleostearic acid, there could be potential for oil production and industrial use as drying oil or in the production of chemical products (Odetoye et al, 2016). However, more studies are needed to assess the potential.…”
Section: Maranthes Polyandramentioning
confidence: 99%